O ensino do Modelo de Leitura Documentária como recurso pedagógico para indexação na perspectiva entre profissional experiente e aprendiz: a aplicação do Protocolo Verbal Interativo na avaliação do uso e da ação de aprendizagem - Borba, Eliane Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
The teaching of indexing procedures by means of the Documentary Reading Model for Indexing of Scientific Articles offers to the apprentice indexer strategies of reading and development of his previous professional knowledgement. The Documentary Reading Model for Indexing of Scientific Articles by Fujita (2003a) is a proposal of improvement and evolution of the methodology of indexing through the indexer's metacognition (non-automatized behaviour as the reader is conscious of how the reading is being carried out), using the knowledgement of textual structures of the reader, relying on strategies of systematic approach of concepts offered in his education. Considering the learning of the documentary reading process in classroom, it is searched into the applicability of this Model as pedagogical resource to apprentice indexers. By means of introspective technique of data collecting of the Interative Verbal Protocol, observing the process of apprehending the methodology, this research reveals difficulties by the apprentice and his development towards more satisfactory grades of carring out the indexing task. It was chosen three students from the second class of Librarianship that had not attended the discipline Indexing and Abstracting and were intested in taking part in the applying of the Verbal Protocol combined with the indexing task. The analysis of the Verbal Protocol's transcriptions shows that the apprentices had difficulties in identifying the concepts of this Model: to choose terms to represent the concepts, to understand the terminology of the medical science and to to set up the terms' form (singular or phrases). Such difficulty is relating to the using of the Reading Model adapted from the original where there was inversion of the concepts action and object. The Interactive Verbal Protocol consists of an innovative methodology functioning as pedagogical resource... (Complete abstract, click electronic address below)
Keywords: Indexação; Protocolo Verbal Interativo; Leitura documentária; Documentary Reading; Indexing; Documentary Reading Model for Indexing Scientific Articles; Interactive Verbal Protocol; Think Aloud Technique